The Effect of Visual Merchandising, Store Atmosphere, and Emotional Response on Impulsive Purchases - Febriansyah Ali; Calvin Sukendra (Journal of Business and Management Review, 2020)
This study aims to determine and analyze the effect of visual merchandising and store atmosphere on emotional response and its impact on impulsive buying. The population uses non-probability techniques using judgmental sampling. The sample consisted of 130 consumers of Mimi Kado. The data analysis technique used is multiple linear regression and the T test. The results showed that visual merchandising has a positive and significant effect on the emotional response of Mimi Kado visitors with a beta coefficient value of 0.219 and t value (2,387)> t table (1,978), shop atmosphere. has a positive and significant effect on the emotional response of Mimi Kado visitors with a beta coefficient value of 0.431 and a value of t count (4.699)> t table (1.978), emotional response has a positive and significant effect on impulsive buying of Mimi Kado visitors with a beta coefficient value of 0.450 and a value of t arithmetic (5.703)> t table (1.978). So it can be suggested the following: take more samples in order to represent perceptions more broadly, take data during peak season, understand priorities in doing research, use the same model but with different research objects, pay attention to linking an indicator with strategic theory , Doing with a planned time and with attention to the respondents only those who have visited and made transactions.